Analysis of User Experience in the WEVERSE Application using the ITIL V3 Service Design Domain : An ENGENE Perspective in Indonesia - Emmanuela Adtrisel Saudale; Penidas Fiodinggo Tanaem (Universitas Islam Indragiri, 2026)
The rapid development of digital technology has changed the way artists and fans interact through community applications such as Weverse. This study aims to evaluate the user experience of Weverse from the perspective of ENGENE (ENHYPEN fans) in Indonesia using the ITIL V3 Domain Service Design approach, as well as to analyze the service quality of the application and provide recommendations for improvement. The research employed a quantitative approach through a survey using a questionnaire instrument developed based on the ITIL V3 Service Design Framework, which consists of six subdomains : Service Catalogue Management, Service Level Management, Capacity Management, Availability Management, Information Security Management,and Supplier Management. The sample consisted of 100 respondents selected using the Slovin formula with a 10% margin of error from an estimated population of 29,937 ENGENE members in Indonesia. Data were analyzed using maturity level analysis and gap analysis. The results show that all subdomains are at Maturity Level 4 (Managed and Measurable), with an average current maturity score of 4.07 and Expected Maturity score of 4.50, resulting in an average gap of 0.43. Among the subdomains, Service Catalogue Management demonstrates the best performance with a current maturity score of 4.21 and the smallest gap of 0.29, while Service Level Management shows the lowest score of 3.89 with the largest gap of 0.61, making it the primary priority for improvement. The findings suggest that the Weverse application has reached the managed stage, where IT service design processes can be systematically measured and monitored. However, continuous improvements are still required to achieve the optimal target of Maturity Level 5 (Optimized).